2019
DOI: 10.1002/bdr2.1565
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of the science of kangaroo (mother) care (skin‐to‐skin contact)

Abstract: In the early 1970s, researchers in Ohio, USA, investigated the effects of “Extra Contact” between mothers and their infants early after birth. The “Extra Contact” consisted of the skin‐to‐skin holding of the newborn infant on the mother's bare chest as soon as possible after birth. In the mid 1970s, Rey and Martinez in Bogota Colombia started investigating the same care method and they called it “Kangaroo Care” (KC). Infants are held upright, skin‐to‐skin on the mother's bare chest. KC, also referred to as Kan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 115 publications
(116 reference statements)
0
36
0
1
Order By: Relevance
“…KC provides a multisensory stimulation, including emotional, tactile, visual and auditory stimuli and is proven to be beneficial for autonomic functioning, improved mother-infant interaction and better sleep wake cycles [ 36 ]. Parent-infant synchrony offers a unique co-regulatory framework for stabilizing physiological parameters and improving neurodevelopmental outcomes that might cause decreases in heart rate during combination therapy [ 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…KC provides a multisensory stimulation, including emotional, tactile, visual and auditory stimuli and is proven to be beneficial for autonomic functioning, improved mother-infant interaction and better sleep wake cycles [ 36 ]. Parent-infant synchrony offers a unique co-regulatory framework for stabilizing physiological parameters and improving neurodevelopmental outcomes that might cause decreases in heart rate during combination therapy [ 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Potentially, there could be clinical advantages to the synergic effects of combination therapy that were not investigated or established in this study. Over the years, numerous studies have demonstrated beneficial outcomes for individual treatments of KC and music therapy regarding neurodevelopmental outcomes, parent-infant bonding, and stress reduction in both infants and parents [ 15 , 18 , 20 , 38 , 45 , 46 , 47 , 48 ]. Future studies should aim to further clarify the effects of LPMT alone and in combination with KC on neurological functioning in the short-term and long-term.…”
Section: Discussionmentioning
confidence: 99%
“…Skin-to-skin contact (SSC) can also be called Kangaroo Mother Care (KMC), which mainly refers to a series of care methods such as premature infants who have skin contact with parturients at birth and breastfeeding [ 9 ]. Because of its simple operation, softness, and high efficiency, it is widely used in the care of newborns [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…KC occurs when an infant or premature infant is dressed in a diaper and held upright to a parent's bare chest. KC has been and continue to be investigated for its effects on a plethora of infant, maternal and family outcomes (Kostandy & Ludington-Hoe, 2019). KC is a beneficial intervention that facilitates the provision of interactions between the newborn and the parent through contact, KC eases the adaptation of the newborn to the external environment in a positive manner and reduces the mortality rate of newborns (Mäkelä et al, 2018;O'Brien et al, 2018;Shorey et al, 2016;Xiaoli et al, 2019).…”
Section: Introductionmentioning
confidence: 99%